2020
DOI: 10.1101/2020.07.21.209163
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Proteomic Differences in the Hippocampus and Cortex of Epilepsy Brain Tissue

Abstract: Epilepsy is a common neurological disorder affecting over 70 million people worldwide, with a high rate of pharmaco-resistance, diverse comorbidities including progressive cognitive and behavioral disorders, and increased mortality from direct (e.g., Sudden Unexpected Death in Epilepsy [SUDEP], accidents, drowning) or indirect effects of seizures and therapies. Extensive research with animal models and human studies provides limited insights into the mechanisms underlying seizures and epileptogenesis, and thes… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 109 publications
0
16
1
Order By: Relevance
“…30 Myelin damage may occur after prolonged seizures and its loss may promote further seizure activity. 31 We found that the mature oligodendrocyte marker myelin basic protein (MBP) is decreased in epilepsy patients compared to non-epilepsy control patients, 18 and it is decreased in the hippocampus of an animal model of epilepsy. 32 However, we found no further decrease in MBP expression in SUDEP or high-risk SUDEP patients when compared to controls in this study, nor was MBP different in our recent RNAseq analysis between MTLE and non-epilepsy controls.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…30 Myelin damage may occur after prolonged seizures and its loss may promote further seizure activity. 31 We found that the mature oligodendrocyte marker myelin basic protein (MBP) is decreased in epilepsy patients compared to non-epilepsy control patients, 18 and it is decreased in the hippocampus of an animal model of epilepsy. 32 However, we found no further decrease in MBP expression in SUDEP or high-risk SUDEP patients when compared to controls in this study, nor was MBP different in our recent RNAseq analysis between MTLE and non-epilepsy controls.…”
Section: Discussionmentioning
confidence: 98%
“…Group sizes were determined based on the number of patients with significant findings as previously reported, [14][15][16] including our earlier studies in epilepsy patients with similar methods. 17,18 Laser Capture Microdissection for Proteomics: FFPE brain tissue blocks containing either hippocampus (lateral geniculate nucleus level) 19 or superior frontal gyrus were sectioned at 8 µm and collected onto laser capture microdissection (LCM) compatible PET slides (Leica). Sections were stained with cresyl violet to localize regions of interest for LCM 20 and air dried overnight in a loosely closed container.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two previous studies have performed proteomics on the DG region of epilepsy patients: Liu et al ( 47 ) compared the proteomes of basal and dispersed granule cells in the hippocampus of MTLE patients with GCD (not including surgical or post-mortem healthy controls), and found that upregulated proteins in dispersed samples were involved in developmental cellular migratory processes. Pire et al ( 48 ) performed proteomic analysis of the hippocampal CA1-3 region, frontal cortex, and DG samples from epilepsy (without specific classification) and control cases, the pathway analysis of altered proteins in the DG involved in mitochondrial dysfunction showed the most enrichment. Interestingly, by analyzing the gene expression profiles of dentate granule cells from surgically resected hippocampal specimens from patients with MTLE with and without HS, Griffin et al ( 19 ) demonstrated that differentially expressed genes were associated with the oxidative phosphorylation pathway, which is generally consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%